Bone healing in critical-size defects treated with new bioactive glass/calcium sulfate: A histologic and histometric study in rat calvaria - Nagata, Maria José Hitomi [UNESP]; Furlaneto, Flavia A. C. [UNESP]; Moretti, Antonio J.; Bouquot, Jerry E.; Ahn, Chul W.; Messora, Michel R. [UNESP]; Fucini, Stephen E. [UNESP]; Garcia, Valdir Gouveia [UNESP]; Bosco, Álvaro Francisco [UNESP] (Wiley-liss, 2010)
This study analyzed histologically the influence of new spherical bioactive glass (NBG) particles with or without a calcium sulfate (CS) barrier on bone healing in surgically created critical-size defects (CSD) in rat calvaria. A CSD was made in each calvarium of 60 rats, which were divided into three groups: C (control): the defect was filled with blood clot only; NBG: the defect was filled with NBG only; and NBG/CS: the defect was filled with NBG covered by CS barrier. Subgroups were euthanized at 4 or 12 weeks. Amounts of new bone and remnants of implanted materials were calculated as percentages of total area of the original defect. Data were statistically analyzed. In contrast to Group C, thickness throughout defects in Groups NBG and NBG/CS was similar to the original calvarium. At 4 weeks, Group C had significantly more bone formation than Group NBG/CS. No significant differences were found between Group NBG and either Group C or Group NBG/CS. At 12 weeks, Group C had significantly more bone formation than Group NBG or NBG/CS. NBG particles, used with or without a CS barrier, maintained volume and contour of area grafted in CSD. Presence of remaining NBG particles might have accounted for smaller amount of new bone in Groups NBG and NBG/CS at 12 weeks postoperative. (C) 2010 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 95B: 269-275, 2010.
Keywords: bone regeneration; bone substitutes; bioactive glass 45S5; calcium sulfate